Controllers and the Magic Kingdom: Corporate Partnership, Synergy and the Limits of Cross-Promotion in Disney and Square Enix’s Kingdom Hearts III (2019) - Denison, Rayna (Loading, 2022)
Who controls the Kingdom Hearts franchise? This article examines this question using a mixed industrial and promotional approach to seek moments of revelation about the creation and status of the Kingdom Hearts franchise for both of its conglomerate co-creators, Disney and Square Enix. Disney’s conglomerated industrial practice has long been assessed for adherence to the concept of synergy. By examining where and how synergy was adopted as an industrial logic within the creation of the Kingdom Hearts franchise, and Kingdom Hearts III in particular, I argue that it is in moments of tension, that we can find the most instructive evidence for who controls the games we play. Following work by Janet Wasko (2001) and Barbara Klinger (1999) in particular, I first look across the shared discursive history of the franchise and then at the promotion of Kingdom Hearts III for instances where synergy breaks down or becomes contested. These, I contend, demonstrate the limits of the logical of synergy in cross-cultural, transindustrial production cultures.